PENGARUH PENDAPATAN, LITERASI ZAKAT, DAN PENDIDIKAN AGAMA TERHADAP KEPATUHAN INDIVIDU DALAM MENGELUARKAN ZAKAT MAAL (STUDI KASUS KJPRI UB) - Muhammad Rizky; Iswan Noor (Islamic Economics and finance in Focus, 2024)
This research aims to analyze the influence of income, zakat literacy, and religious education on individuals' compliance in paying zakat al-maal (a case study of KJPRI UB). The method used in this research is a quantitative case study. The data analysis employed logistic regression analysis. The results indicate that income, zakat literacy, and religious education have a significant positive influence on compliance in paying zakat al-maal simultaneously. Income does not have a partial effect on individuals' compliance in paying zakat al-maal. Meanwhile, zakat literacy and religious education have a positive partial effect on individuals' compliance in paying zakat al-maal.